Relationship between Sphk1/S1P and microRNAs in human cancers. (17th May 2020) - Khoei, Saeideh Gholamzadeh; Sadeghi, Hamid; Samadi, Pouria; Najafi, Rezvan; Saidijam, Massoud
Abstract: Sphingosine kinases type 1 ( SphK1 ) is a key enzyme in the phosphorylation of sphingosine to sphingosine 1‐phosphate (S1P). Different abnormalities in SphK1 functions may correspond with poor prognosis in various cancers. Additionally, upregulated SphK1 /S1P could promote cancer cell proliferation, angiogenesis, mobility, invasion, and metastasis. MicroRNAs as conserved small noncoding RNAs play major roles in cancer initiation, progression, metastasis, etc. Their posttranscriptionally mechanisms could affect the development of cancer growth or tumorigenesis suppression. The growing number of studies has described that various microRNAs can be regulated by SphK1, and its expression level can also be regulated by microRNAs. In this review, the relationship of SphK1 and microRNA functions and their interaction in human malignancies have been discussed. Based on them novel treatment strategies can be introduced. Abstract : SphK1‐microRNA dual functions in cancers